Capacidad de inhibición de cuatro extractos de arvenses y mucílago de cacao Theobroma cacao, sobre la Rottboellia exaltata y Eleusine indica. - Ormaza Molina, Andrea Katherine (2017)
In this study the capacity of inhibition of four extracts of weeds and cocoa mucilage Theobroma cacao L, on the Rottboellia exaltata L. f. and Eleusine indica (L) Gaertn. The research was carried out at the La María experimental farm of the State Technical University of Quevedo, with the purpose of determining the effect on aqueous extracts of coquito Cyperus rotundus L., cerbatana Synedrella nodiflora, bledo Amarantus sp, venadillo Conyza bonarienses and mucilage cocoa Theobroma cacao L., on Rottboellia exaltata L. f. and Eleusine indica. A Completely Randomized Blocks Design (D.B.C.A) was applied, with 5 treatments plus 2 controls (glyphosate chemical and absolute water) in 4 repetitions. The variables studied were subjected to the analysis of variance and the Túkey test was used at 95% probability. We evaluated the descriptive toxicity of the effect of the treatments on Rottboellia exaltata and Eleusine indica measured by means of the Rochecouste scale, the percentage of control of weeds by means of the ALAM scale. The results indicate that the vegetable extracts and cocoa mucilage Theobroma cacao L., used pure in the control of the treadmill Rottboellia exaltata and straw of donkey Eleusine indica, highlight an allelopathic effect that exerts a control on the 2 weeds mentioned with control averages between 80% and 100%. These percentages in the 50% test of cocoa extract and mucilage Theobroma cacao L., with water reached an average of 100% control considered excellent, followed by the extracts of bledo (Amarantus sp.), cerbatana (Synedrella nodiflora), venadillo (Conyza bonarienses), with control averages between 80% and 90% considered very good. In the case of coquito (Cyperus rotundus L.) with averages between 75% and 80% considered good. Regarding the phytotoxic effects on the treadmill Rottboellia exaltata and donkey straw, Eleusine indica reached averages between 8 and 10%, which means that the weeds presented dead stems between 50% and the total death of the treated weeds. Keywords: Plant extracts, control, Rottboellia exaltata and Eleusine indica.